Diversitas Genetik Populasi Padi (Oryza sativa L.) Payo di Kabupaten Kerinci Provinsi Jambi Berdasarkan Marka Morfologi: Diversitas Genetik Populasi Padi (Oryza sativa L.) Payo di Kabupaten Kerinci Provinsi Jambi Berdasarkan Marka Morfologi - Sosiawan Nusifera; Yulia Alia; Ardiyaningsih Puji Lestari; Muhammad Maulana (Universitas Bangka Belitung, 2020)
Payo rice is one of the local rice varieties from Kerinci, Jambi Province. It is popular in Jambi due to its texture and good taste qualities. Farmer preferences changing to modern varieties and massive infrastructure development lead to Payo rice extinction. This research was aimed to find out the genetic diversity of Payo rice population-based on morphological markers in Kerinci area. Non-experimental research was conducted to obtain the data by direct survey or in situ characterization. Samples were determined using the proportionate stratified random sampling method. Morphological characters were measured both quantitatively and qualitatively based on IRRI and WARDA guidelines with few modifications. Quantitative data were analyzed using the coefficient of variability, while qualitative data were analyzed using relative diversity index (J). Genetic diversity among individual members of the population was analyzed using cluster analysis and presented in a dendrogram. Results indicated that several morphological characters, which were number of productive tillers, angle of flag leaf, threshability, number of empty grain, color of ligule, color of auricle, leaf surface, and color of grain, showed large variability, while others were narrow. Overall, relatively large genetic diversity was observed in Payo rice population in Kerinci area. At least 21 different genotypes were identified in the existing population.